The moviegoer - Percy, Walker, 1916-1990 (FSG classics, 2019)
Binx Bolling, a young New Orleans stockbroker, fills his days with movies and casual sex. His life offers him nothing worth retaining; what he treasures are scenes from The Third Man or Stagecoach, not the personal experiences he knows other people hold dear. On the cusp of turning thirty, however, something changes: At Mardi Gras, he embarks on a quest for some form of authentic experience. The consequences of Binx's quest, on both himself and his unstable cousin Kate, prove outrageous, absurd, moving, and indelible. - Resumé vydavatel